A population survey of the endangered White-headed Duck Oxyura leucocephala in Kazakhstan shows an apparently increasing Eastern population. Issue 1 (2nd January 2019) - Koshkina, Alyona I.; Koshkin, Alexey V.; Timoshenko, Alexey Y.; Koshkin, Artyom A.; Schielzeth, Holger
ABSTRACT: Capsule: Surveys of the White-headed Duck Oxyura leucocephala at key breeding and staging sites in Kazakhstan suggest a positive trend for the migratory Eastern population and an underestimation of the global population. Aims: To review and update the population estimate and distribution status of the White-headed Duck in Kazakhstan using the most recent survey data. Methods: Distribution and population estimates were derived from a compilation of all published and unpublished data and a series of targeted surveys in 2013–17, covering breeding, post-breeding and migration periods at key sites in north-central Kazakhstan. Results: Numbers of White-headed Ducks were particularly high in the post-breeding and autumn migration period. There was a positive population trend across the past two decades, including high counts in 2016 and 2017, with more than 20 000 and about 7500 individuals, respectively, suggesting a population increase. Breeding records were scattered and overall low in numbers, but likely partly overlooked. Conclusion: The global population size of the White-headed Duck is currently considerably underestimated. The positive trend reflects the overall improvement in the status of the Eastern population. However, aggregation at relatively few sites represent a potential conservation concern. The breeding sites that are a source for the migratory aggregations in north-central Kazakhstan are still to be discovered.